The Emerging Role of Intracardiac Echocardiography (ICE) in Left Atrial Appendage Closure (LAAC) - Jhand, Aravdeep; Goldsweig, Andrew M. (Current cardiology reports, 2023)
Purpose of Review Intracardiac echocardiography (ICE) has emerged as a powerful imaging tool to guide percutaneous left atrial appendage closure (LAAC). Herein, we review an imaging protocol for ICE-guided LAAC and discuss the evidence for its use. Recent Findings Standardized imaging protocols have been proposed but have not been fully validated. ICE imaging yields similar procedural and clinical outcomes when compared to transesophageal echocardiography (TEE) to guide LAAC. Despite benefits of avoiding general anesthesia, TEE, and multiple physicians for LAAC procedures, ICE imaging remains under-utilized. Novel ICE catheters with 3D imaging capabilities may improve accuracy and efficiency of LAAC device implantation. Summary ICE guidance is feasible, safe, and effective for LAAC. As the field evolves, further studies will be necessary to assess this technological advancement in imaging guidance.